Comparative Compound Sentence (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article gives information on the type of sentence, comparative compound sentence without conjunctions in comparison in languages. It is different in both languages. This sentence  is connected by tone using comma and is given as separate type of  composite sentence in Uzbek. Whereas it is connected by semicolon and is referred as compound sentence in English